1986
DOI: 10.1097/00000658-198603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

PMN Superoxide Radical Production Following a Metabolic-Endocrine Simulation of Trauma

Abstract: Serious infections following major trauma remain inexplicably high. Metabolic and endocrine changes after injury have been suggested as being responsible for many of the documented defects in the polymorphonucleocyte (PMN). The in vitro bactericidal activity of normal human PMNs has been examined in this laboratory by assaying the activity of the PMN membrane bound enzyme NADPH oxidase and hence O2- production of the PMN in a metabolic/endocrine milieu designed to simulate moderately severe trauma. This was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…While their absolute necessity for the healing of sterile surgical wounds is debated [30,31], there is clear evidence that neutrophil dysfunction leads to increased infectious complications [32]. Previous studies have demonstrated phenotypic alterations of circulating neutrophils in response to catecholamine stimulation [17,[21][22][23][24][33][34][35][36][37][38]; however, the effect of these stimuli on recruited wound neutrophils is unknown [39]. The present study is the first to demonstrate NE-mediated alterations in the process of phagocytosis by wound neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…While their absolute necessity for the healing of sterile surgical wounds is debated [30,31], there is clear evidence that neutrophil dysfunction leads to increased infectious complications [32]. Previous studies have demonstrated phenotypic alterations of circulating neutrophils in response to catecholamine stimulation [17,[21][22][23][24][33][34][35][36][37][38]; however, the effect of these stimuli on recruited wound neutrophils is unknown [39]. The present study is the first to demonstrate NE-mediated alterations in the process of phagocytosis by wound neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for the priming of neutrophils in the early phase of myocardial infarction is not clear, although several explanations have been proposed: activation of receptors [24], metabolic stimulation by stress hormones [25], post-traumatic endocrine stimulation [26] and secretion of cytokines [27]. The increased superoxide release 402 K. RIESENBERG et al by stimulated and particularly unstimulated neutrophils of MI patients indicates that the neutrophils are in a primed state.…”
Section: Discussionmentioning
confidence: 99%
“…Factors which have been attributed to endotoxic shock pulmonary response include release of vasoactive substances [11], me chanical blockage of capillaries by platelet aggregates [12,13], and degranulated and fragmented leukocytes sequestered in several vascular beds following infusion of live E. coli in baboons [ 14], findings later confirmed by others [8,15], It is damage to the lung capillary endothe lium by attached leukocytes which leads to shock [14], with a particularly high leukocyte destruction rate in endotoxin-induced shock [16], but to date most studies have been in vitro. Now that techniques for labeling leu kocytes with indium-111 oxine are available, it is possible to investigate the sequence of events concerning leukocyte behavior during endotoxin-induced shock [10].…”
Section: Discussionmentioning
confidence: 98%
“…Platelet sequestration in lung capillaries during endotoxic shock is well documented [1][2][3], as well as leukopenia occurring in sev eral species [4], In 1961, Athens et al [5] hypothesized that the disappearance of neu trophils from circulation was the result of their sequestration in capillaries, but it was 10 years before it was described occurring in pulmonary capillaries, causing injury and possibly leading to the adult respiratory dis tress syndrome (ARDS) [6], Several in vitro studies confirmed these findings [7][8][9], There are no published in vivo studies on the dynamic behavior of leukocytes in the lungs or other organs during endotoxin-inbe the pathogenic factor for lung, liver and duced shock, although Cooper et al [10] recently reported in vivo radiolabeled leuko cyte kinetics in sheep after thrombin-in duced intravascular coagulation.…”
Section: Introductionmentioning
confidence: 99%